Trilostane exerts antidepressive effects among wild-type, but not estrogen receptor β knockout mice - Koonce, Carolyn J. (2009)
Women with estrogen receptor (ER) positive breast cancer, who are treated with the ER blocker, tamoxifen, have an increased risk of depression. Trilostane, a 3β-hydroxysteroid dehydrogenase inhibitor, is now being used to treat tamoxifen-insensitive breast cancer. In-vitro assays show that trilostane may have actions through ERβ. Results of in-vivo research shows that actions at ERβ may underline some antidepressant effects of estrogen. We hypothesized that trilostane may exert antidepressive effects in the forced swim in part due to actions through ERβ. Trilostane (25 mg/kg, intraperitoneally), compared with vehicle, had significant antidepressant-like effects but only when administered to wild-type, not ERβ knockout, mice. Thus, actions of trilostane through ERβ may underlie some of its antidepressant-like effects.